Assessment of lymphovascular invasion in early stage endometrial carcinoma -a retrospective study - Ambreen Moatasim; Zujajah Hameed; Imran Ahmad (BMC, 2021)
Abstract Introduction Endometrial carcinoma is associated with several known prognostic factors. Recently, lymphovascular invasion (LVI) has gained a prominent position in the risk assessment of early endometrioid endometrial carcinoma, in identifying patients who can benefit from adjuvant radiation therapy. This study aims to assess LVI in early-stage endometrioid endometrial carcinoma accurately with emphasis on its extent /grading. We also propose a few local recommendations for improving LVI reproducibility in endometrial carcinoma to guide future studies. Methods The duration of this retrospective study was 2 years. Early-stage I (Ia and Ib), and grade 1 and 2 endometrioid endometrial carcinomas were included. 03 reviewers independently recorded their findings on H&E stained slides. LVI was graded as none, focal and substantial. In discordant cases, immunohistochemical stain CD 31 was used. All the data was entered in the statistical software SPSS version 26 and analyzed for frequencies. The relationships between various histological parameters assessed and the degree of reproducibility for LVI amongst various observers were also determined. Results Out of a total of 70 cases of endometrioid carcinoma diagnosed on hysterectomy specimen, only 32 met our inclusion criteria. The rate of LVI positivity was 6.3 %, 34.4 %, and 37.5 % respectively for reviewers 1, 2, and 3. The degree of reproducibility in LVI assessment and LVI grading was significant amongst reviewers 2 and 3. Also, a significant association was drawn between tumor grade and LVI. Conclusion Despite limitations in our study we recommend including both LVI assessment and grading in routine reporting formats locally. By adding a second reviewer in LVI assessment and using CD31 in discrepant cases LVI positivity can be significantly increased.